2022
DOI: 10.3390/jcm11133572
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intensive Vibratory Treatment with a Robotic System on the Recovery of Sensation and Function in Patients with Subacute and Chronic Stroke: A Non-Randomized Clinical Trial

Abstract: Background: Sensory–motor deficits are frequent and affect the functionality after stroke. The use of robotic systems to improve functionality and motor performance is advisable; therefore, the aim of the present study was to evaluate the effects of intensive, high-frequency vibration treatment administered with a robotic system in subacute and chronic stroke patients in terms of upper limb sensitivity, motor function, quantity and quality of movement, and quality of life. Methods: A simple-blind, non-randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 47 publications
0
11
0
2
Order By: Relevance
“…However, in the case of the MAL-30 scale, it corresponds to an instrument that is widely used in clinical practice; thus, it requires the support of the professionals who use it. Likewise, the translation of this instrument has been used in other studies [ 20 , 31 , 32 , 33 , 34 ]. This content validation process can therefore be considered as already completed for this assessment tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the case of the MAL-30 scale, it corresponds to an instrument that is widely used in clinical practice; thus, it requires the support of the professionals who use it. Likewise, the translation of this instrument has been used in other studies [ 20 , 31 , 32 , 33 , 34 ]. This content validation process can therefore be considered as already completed for this assessment tool.…”
Section: Discussionmentioning
confidence: 99%
“…The MAL-30 measure has been validated in several countries [ 20 , 22 , 26 , 27 , 28 , 29 , 30 ] and has been translated into Spanish, but it was uniquely adapted to the Hispanic American population [ 20 , 31 ]. However, some studies that were carried out in Spain [ 32 , 33 , 34 ] used this version that was translated into Spanish but not validated for this population. Because of this, despite the fact that it is a scale that is currently being used in various studies, the MAL assessment instrument has not been validated for post-stroke patients in the Spanish population.…”
Section: Introductionmentioning
confidence: 99%
“…Previous preliminary studies have explored the effectiveness of the Amadeo ® system for the recovery of motor functions after stroke [ 19 , 20 ]. Recently, a clinical trial conducted by our research group showed that the use of this system, in combination with conventional intervention, produces partial improvements in sensory and motor function in daily upper limb performance in terms of quantity and quality of movement, and in the overall performance of basic and instrumental activities of daily living [ 21 ]. However, it is still unknown whether baseline levels of sensory and motor function, as well as previous performance levels, are related to improvements in upper limb and daily activity performance following this intervention.…”
Section: Introductionmentioning
confidence: 99%
“…However, most research has explored the effectiveness in terms of gait function and performance [ 22 ], or in terms of upper limb motor function [ 23 , 24 ], and only few studies have focused on the effectiveness of robot systems in terms of both sensory and motor function and upper limb or overall performance [ 25 ]. While findings of our previous work suggest that a combination of conventional treatment and a robot system intervention may lead to partial improvements in sensorimotor function and both upper limb and overall daily performance [ 21 ], the relationship between baseline levels of function and performance and post-intervention improvements is still unclear. Exploring this relationship would contribute to a better prognosis and understanding of the specific variables predicting post-intervention outcomes following a stroke, and it would allow for a more tailored approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation